Effects of Olive Oil and Its Minor Components on Cardiovascular Diseases, Inflammation, and Gut Microbiota - Marcelino, Gabriela; Hiane, Priscila Aiko; Freitas, Karine de Cássia; Santana, Lidiani Figueiredo; Pott, Arnildo; Donadon, Juliana Rodrigues; Guimarães, Rita de Cássia Avellaneda (Nutrients, 2019)
Olive oil is one of the main ingredients in the Mediterranean diet, being an important ally in disease prevention. Its nutritional composition is comprised of mainly monounsaturated fatty acids, with oleic being the major acid, plus minor components which act as effective antioxidants, such as hydroxytyrosol. Studies have shown that the consumption of olive oil, as well as its isolated components or in synergism, can be a primary and secondary protective factor against the development of cardiovascular diseases since it reduces the concentrations of low-density lipoproteins and increases the concentration of high-density lipoproteins. Furthermore, it exerts an influence on the inflammatory markers, such as interleukin-6 and tumor necrosis factor, which are pro-inflammatory agents in the body. The components present in olive oil are also associated with the promotion of intestinal health since they stimulate a higher biodiversity of beneficial gut bacteria, enhancing their balance. The objective of this review is to present recent data on investigated effects of olive oil and its components on the metabolism, focused on cardiovascular diseases, inflammation, and gut biota.